Keys to The gift : a guide to Nabokov's novel - Leving, I͡Uriĭ (Studies in Russian and Slavic literatures, cultures and history., 2011)
Yuri Leving's Keys to "The Gift": A Guide to Vladimir Nabokov's Novel is a new systematization of the main available data on Nabokov's most complex Russian novel, The Gift (1934-1939). From notes in Nabokov's private correspondence to scholarly articles accumulated during the seventy years since the novel's first appearance in print, the work draws from a broad spectrum of existing material in a succinct and coherent way, as well as providing innovative analyses. The first part of the monograph, "The Novel," outlines the basic properties of The Gift (plot, characters, style, and motifs) and reconstructs its internal chronology. The second part, "The Text," describes the creation of the novel and the history of its publication, public and critical reaction, challenges of the English translation, and post-Soviet reception. Along with annotations to all five chapters of The Gift, the commentary provides insight into problems of paleography, featuring unique textological analysis of the novel based on the author's study of the archival copy of the manuscript. --From publisher's description